A practical study of factors that affect forward osmosis experiments - Teo, Jia En. (2010)
Reverse osmosis (RO) can provide ultra pure water but is not an ideal process as high pressure is required to overcome osmotic pressure in sea-water. The high pressure requires large amount of electrical energy and this in turn causes other environmental issues like burning of fossil fuels and pollution.